Obstetric and new born outcome in HIV infected pregnant women: a prospective cohort study in Bangalore Medical College Hospitals, India - Desai, Rashmi S.; Shivamurthy, Geetha; Desai, Sameer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The effect of HIV on obstetric complications is known to vary across regions of world. The variation may be due to HIV infection per se or it may be due to complex interaction of related medical and social conditions that affect pregnancy. Incidence of these obstetric complications in HIV infected pregnant women is not well reported in India. So, this prospective cohort study was carried to observe the demographics and incidence of obstetrics complications like abortions, still birth, premature rupture of membranes, preterm delivery, opportunistic infections in HIV infected pregnant women. Methods: All pregnant women who were screened positive for HIV test, irrespective of their gestational age were included in the study. Apart from routine obstetric care, CD4 cell count was carried out. The patients were followed up till term, delivery and up to 6-week postpartum period. Obstetric outcomes like incidence of abortion, intrauterine death, preterm delivery and premature rupture of membrane were noted. Baby`s birth weight and the incidence of maternal opportunistic infection were noted and correlated with maternal CD4 cell count. Results: Maternal HIV infection is associated pre-term labour in 34.5%, PROM in 30%, low birth weight in 52.3%. Increased incidences of these adverse outcomes have an inverse relationship with CD4 count. Conclusions: Maternal HIV infection is associated with increased incidence of adverse obstetric outcome and opportunistic infection, and their incidences increase with lower CD4 count.